Optimization of Laser-Patterned Superhydrophilic–Superhydrophobic Surfaces on 304 Stainless Steel for Enhanced Fog Water Collection - Hongda Chen; Jingnan Zhao; Wenjian Ma; Zhiquan Guo; Yuanchen Cui (Optics)
This study focuses on creating micro-nano structures on the surface of 304 stainless steel using nanosecond lasers to achieve superhydrophobicity for fog water collection experiments in a fog chamber. By adjusting pattern parameters, an uneven wettability surface was processed, and six samples were placed at different positions in the chamber to study water collection efficiency from various surfaces. The experimental results indicate that the water collection efficiency of the patterned superhydrophobic surface is superior to that of the original surface, with the front sample collecting 0.4524 ± 0.005 g of water, representing a 90.38% improvement. As the kinetic energy of the fog flow gradually diminishes, a total of 1.1913 ± 0.005 g of water was collected, achieving a 60.25% improvement. The study also investigates the durability and optimal temperature conditions for fog water collection, ultimately achieving 1.4781 ± 0.005 g of water collection in a 5 °C fog environment, resulting in a 98.83% enhancement.